Analysis of the Effect of Growth, Profitability, Interest Rates, Inflation and Asset Structure on Firm Value With Dividend Policy as an Intervening Variable - Siham Muhammad; Apriliana Kurniasari (Iqtisad: Reconstruction of Justice and Welfare for Indonesia, 2022)
This research is to analyze the effect of growth, profitability, interest rates, inflation, and asset structure on firm value. On the other hand, this research also analyzes dividend value as an intervening variable. used path analysis to analyze the data in this study. Of the 30 populations in this study, the samples that came out after using purposive sampling were from 7 companies. The purpose of this study was to determine and analyze the effect of growth, profitability, interest rates, inflation and asset structure on dividend policy and firm value. The results of this study indicate that growth and profitability have a significant effect on dividend policy; however, interest rates, inflation, and asset structure have no significant effect on dividend policy. Growth and profitability have a significant effect on firm value, but interest rates, inflation, and asset structure have no significant effect on firm value. Dividend policy has a significant effect on firm value. Growth, profitability, interest rates, inflation, and asset structure have no significant effect on firm value through dividend policy. Abstrak Penelitian ini untuk menganalisis pengaruh pertumbuhan, profitabilitas, suku bunga, inflasi, dan struktur aktiva terhadap nilai perusahaan. Di sisi lain, penelitian ini juga menganalisis nilai dividen sebagai variabel intervening. menggunakan analisis jalur untuk menganalisis data dalam penelitian ini. Dari 30 populasi dalam penelitian ini, sampel yang keluar setelah menggunakan purposive sampling adalah sebanyak 7 perusahaan. Tujuan penelitian ini untuk mengetahui dan menganalisis pengaruh pertumbuhan, profitabilitas, suku bunga, inflasi dan struktur aset terhadap kebijakan dividen dan nilai perusahaan. Hasil penelitian ini menunjukkan bahwa pertumbuhan dan profitabilitas berpengaruh signifikan terhadap kebijakan dividen; namun suku bunga, inflasi, dan struktur aset tidak berpengaruh signifikan terhadap kebijakan dividen. Pertumbuhan dan profitabilitas berpengaruh signifikan terhadap nilai perusahaan, tetapi suku bunga, inflasi, dan struktur aset tidak berpengaruh signifikan terhadap nilai perusahaan. Kebijakan dividen berpengaruh signifikan terhadap nilai perusahaan. Pertumbuhan, profitabilitas, suku bunga, inflasi, dan struktur aset tidak berpengaruh signifikan terhadap nilai perusahaan melalui kebijakan dividen. Keywords: Pertumbuhan; Profitabilitas; Suku Bunga; Inflasi; Struktur Aset; Nilai Perusahaan; Kebijakan dividen.